2003
DOI: 10.1007/s00285-002-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Year class coexistence or competitive exclusion for strict biennials?

Abstract: We consider a discrete time model of semelparous biennial population dynamics. Interactions between individuals are modelled with the aid of an "environmental" variable I. The impact on and the sensitivity to the environmental condition is age specific. The main result is that competitive exclusion between the year classes is possible as is their coexistence. For moderate values of the basic reproduction ratio R(0) there is a strict dichotomy: depending on the other parameters we either find competitive exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…In the second case, most juveniles die in years when adult density is high; there will be few adults in the next year but many juveniles, which enjoy high resource abundance and mature into many adults by the year after. These cycles are essentially the same as the single cohort dynamics found by Bulmer (1977) and analyzed in detail by Davydova et al (2003;see Discussion). In this paper, we concentrate on stationary spatial pattern formation and thus do not pursue temporal cyclic behavior further.…”
Section: Dynamics Of An Isolated Populationmentioning
confidence: 70%
“…In the second case, most juveniles die in years when adult density is high; there will be few adults in the next year but many juveniles, which enjoy high resource abundance and mature into many adults by the year after. These cycles are essentially the same as the single cohort dynamics found by Bulmer (1977) and analyzed in detail by Davydova et al (2003;see Discussion). In this paper, we concentrate on stationary spatial pattern formation and thus do not pursue temporal cyclic behavior further.…”
Section: Dynamics Of An Isolated Populationmentioning
confidence: 70%
“…Bulmer [2] showed that severe inter-class competition stabilizes perfect periodicity and predation reinforces the tendency (e.g. see also [6,9,24]). Appendix 1 shows that (H6) can be realized when inter-class competition is severe.…”
Section: Is Asymptotically Stable In the Subsystem X = 0 If And Only mentioning
confidence: 99%
“…Mathematically, the dynamics of semelparous populations can be described by a discrete-time nonlinear Leslie matrix model (Cushing 2006;Davydova 2004;Davydova et al 2005;Diekmann and van Gils year;Drissche and Zeeman 1998;Kon 2005;Kon and Iwasa 2007;Mjolhus et al 2005). The phenomenon of periodical insects can be explained by the invariance of coordinate axes and hyperplanes of the full life cycle map (Davydova et al 2003) and the existence of heteroclinic cycles connecting different year cycles (Cushing 2009;Diekmann and van Gils 2009). Diekmann and van Gils (2009) demonstrated that the n-dimensional discrete-time Leslie matrix model can be reduced to a cyclic replicator system on the (n − 1) dimensional simplex and classified the repertoire of the dynamical behavior for n = 2 and 3.…”
Section: Introductionmentioning
confidence: 99%